Do triathletes periodize their diet and do their mineral content, body composition and aerobic capacity change during training and competition periods? - Durkalec-Michalski, K.; Glówka, N.; Nowaczyk, P. M.; Laszczak, A.; Gogojewicz, A.; Suliburska, J. (Nutrients)
The triathlon is a demanding endurance multisport, which may strongly affect the nutritional status of athletes. The aim of this study was to find whether there are any differences in energy value and nutrient intake, body mass and body composition, aerobic performance and hair mineral status between training and competition periods and to assess whether there is a link between hair mineral content and physical capacity and nutrition. This observational study covered 20 triathletes aged 32 ± 7 years. The results of our study indicated performance improvement during the competition period (longer time to exhaustion (p = 0.025) and lower maximal oxygen uptake at the ventilatory threshold (%VO2max_VT; p = 0.047)). However, no differences were recorded in nutrition and body composition between two training vs. competition periods. There was a significant depletion in hair iron content during the competition period (p = 0.010). Furthermore, there were significant relationships between hair calcium content and absolute maximal oxygen uptake and %VO2max_VT during the training period. It is necessary to introduce nutritional education in the group of triathletes focused on exercise-oriented nutritional periodization following the requirements of the training and competition periods, thus preventing the risk of nutrient deficiencies.